Chemotherapy-induced toxic epidermal necrolysis in a patient with multiple myeloma, a case report and literature review - X, Rui; W, Meidan; W, Gongqiang; Z, Longyi; W, Xiaoxia; C, Wei; W, Chenhui (Frontiers in Oncology, 2023)
Toxic epidermal necrolysis (TEN) and Stevens-Johnson syndrome (SJS) are rare dermatological conditions generally caused by certain drugs. In this case report, we describe a patient with multiple myeloma (MM) who developed TEN after being treated with the Velcade-lenalidomide-dexamethasone (VRD) regimen and the patient eventually recovered after a 30-day hospitalization. In this report, we review the use of lenalidomide and other immunomodulatory drugs for the treatment of hematological malignancies, which have been known to induce SJS/TEN. We also suggest that some combinational therapies may enhance the functions of T cells and natural killer (NK) cells, which are necessary for prolonging patients’ survival. However, this may also result in an exaggerated immune response and high plasma concentrations of immune cells, which can potentially trigger SJS/TEN.